Storms and Hurricanes - Bone, Emily; Chandler, Sam; Dawes, Will; Kelly, Alison; Olley, Mike; Reese, Alice; Scott, Kimberley; Trend, Roger; Weston, Paul (London Usborne, 2012)
What makes thunder and lightning, and why do hurricanes do so much damage? This book lays out the answers and much more, using photographs, clear step-by-step illustrations and simple text
Science (Nature)
Keywords: Biology